Contextualising the Regeneration of Africa’s Indigenous Governance and Management Systems and Practices - BC, Basheka (Administratio Publica, 2020)
The primary aim of this article is to remind contemporary public administration analysts and policy-makers of the need to position indigenous governance management systems and practices within mainstream intellectual discourse. The African continent has suffered a tormented history. This is partly due to the different historical periods and deliberate efforts to Westernise all explanations concerning African governance, knowledge management systems and practices. Centuries-old indigenous African knowledge regarding the management of societal affairs has been overshadowed by colonialism, neocolonialism, global capitalism and the promotion of Western organisational management/leadership practices. Furthermore, Western cultures showed intellectual arrogance by painting anything African in a negative light. Yet, indigenous African countries had their own governance systems and knowledge management practices that are worthy of any academic and intellectual theorisation and discourse. While the article does not argue that these indigenous systems and practices are flawless, the societies under study exhibited important features that can provide a lens for understanding contemporary challenges surrounding public administration and theorisation.